The Forgotten Medium: Hoso Kanri Kyoku and the Beginning of National Broadcasting in Indonesia - Widya Fitria Ningsih (Lembaran Sejarah, 2016)
This essay examines Hoso Kanri Kyoku, a bureau of radio centre and regulation, which has been much underestimated and understudied. It became an instrument of mass mobilization and mass psychology in the Japanese occupation period. The essay sees also the pivotal role of this institution in disseminating ideas of ‘ke-Indonesiaan’. The aim of this essay is to show how the transformation process of the institution after the proclamation of Indonesian independence. The essay uses historical archival research as a method of data collection. This essay have indirectly presented that the Soeharto regime continued the legacy of the Japanese Military regime in Indonesia.